Front Cover: Hierarchical Multiporous Nickel for Oxygen Evolution Reaction in Alkaline Media (ChemCatChem 24/2019). Issue 24 (3rd December 2019) - Assavapanumat, Sunpet; Ketkaew, Marisa; Garrigue, Patrick; Lapeyre, Véronique; Reculusa, Stéphane; Wattanakit, Chularat; Kuhn, Alexander
Abstract : The Front Cover shows the combination of macroporous and mesoporous features in a nickel layer is tested for the electrochemical oxygen evolution reaction. In their Full Paper, Chularat Wattanakit, Alexander Kuhn and co‐workers obtain highly organized hierarchical porous nickel by combining a hard‐ and soft‐template method to increase its electrocatalytic performance and stability during oxygen evolution reaction. This example illustrates a promising strategy for the rational design of high‐performance porous metals, not only in the frame of water electrolysis, but also for other electrocatalytic applications. More information can be found in the Full Paper by Sunpet Assavapanumat et al. on page 5951 in Issue 24, 2019 (DOI: 10.1002/cctc.201901509 ).